Anti-inflammatory abietane diterpenoids from the seeds of Podocarpus nagi. (September 2017) - Feng, Zhe-Ling; Li, Dan; Liu, Qian-Yu; Liu, Jing-Xin; Huang, Li; Zhang, Qing-Wen; Wang, Yi-Tao; Lin, Li-Gen
Graphical abstract: Highlights: Three new abietane diterpenoids were isolated from the seeds of Podocarpus nagi . Compound1 inhibited LPS-induced NO production with IC50 value of 5.38 ± 0.17 μM. Compound1 suppressed iNOS expression in a dose-dependent manner. Compound1 inhibited inflammatory response via MAPK and NF-κB signaling pathways. Abstract: In searching for naturally occurring anti-inflammatory agents, three new abietane-type diterpenoids, named 16-hydroxylambertic acid (1 ), 7-oxo-18-hydroxyferruginol (2 ), and 5 α, 12-dihydroxy-6-oxa-abieta-8, 11, 13-trien-7-one (3 ), were isolated from the seeds of Podocarpus nagi, together with three known compounds. The structures of the new compounds were elucidated by extensive analysis of NMR and HR-ESIMS data. All the new compounds were tested for nitric oxide (NO) inhibitory activities on lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Compound1 significantly inhibited NO production with IC50 value of 5.38 ± 0.17 μM, and suppressed inducible NO synthase (iNOS) expression in a dose-dependent manner, which were mediated through inhibiting the mitogen-activated protein kinases (MAPKs) and nuclear factor-κB (NF-κB) activation.